METODE SOCIAL CASEWORK SATUAN BAKTI PEKERJA SOSIAL (SAKTI PEKSOS) DALAM PENANGANAN KORBAN KEKERASAN PADA ANAK DI DINAS SOSIAL KOTA KENDARI - Nadiah Imasturahma; Bahtiar Bahtiar; Amin Tunda; Lutfiana Nur Azizah (WELL-BEING: Journal of Social Welfare, 2023)
This study aims to determine the stages of the social casework method carried out by Sakti Peksos in handling victims of violence against children, the supporting and inhibiting factors for Sakti Peksos in providing assistance, and the results of the social casework method carried out by Sakti Peksos to restore the social functioning of victims of violence against children in cities. Kendari. This type of research uses a qualitative approach with descriptive methods. The determination of informants in this study used a purposive sampling method so that the informants in this study were Sakti Social Workers, Head of the Social Rehabilitation Division, two child victims of physical violence, two child victims of sexual violence and two victim families. The data sources used in this research are primary data and secondary data. Data collection techniques used are observation, interview, and documentation methods. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results showed that first, the stages of the social casework method were 1) the research stage which consisted of intake, context, and contracts, 2) the assessment stage which consisted of assessment and intervention plans, 3) the intervention stage which consisted of interventions and follow-up plans (RTL), 4) termination stage. Second, the supporting factors are 1) the scientific side of Sakti Peksos, 2) a large network of collaborations, 3) trust from other parties, while the inhibiting factors are 1) lack of human resources, 2) time, and 3) social services do not yet have shelters. Third, the results of the social case work assistance method carried out by Sakti Peksos can restore the social functioning of victims of violence against children in Kendari City namely, 1) children who are victims of violence are able to carry out their duties, roles and functions, 2) children who are victims of violence are effective towards themselves, other people, and their environment, 3) children who are victims of violence can pursue their hobbies, 4) children who are victims of violence fight for their goals/hope/aspirations in life.